Usage of Creative Dance as a pedagogy forexperiential learning in Indian primary school children. - et. al., Dr. Swetha N, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In Indian schools, Dance is taught as an art form and much as a recreation to students. Aim : The main purpose of this research paper is to highlight the literature that states the benefits of using dance as a pedagogy to teach children in schools. The paper also aims to understand the benefits dance that can be used as an experiential learning among the age group of 5 to 10 years in mainstream CBSE schools in India. Methodology: Many databases were searched including the key words and it was concluded that creative dance as a pedagogy can be used as an experiential learning at schools. Results: The advantages of creative dance in cognition, physical, socio emotional aspects can be observed. Development of creative dance as experiential learning with right assessment parameters can be effective in carrying out the implementation of the curriculum.